Serum iron Profile of Patients with Sickle Cell Disease and its Association with Socio-demographic Characteristics and Duration of Diagnosis - Kamar, Sher Bahadur; Pandey, Hemraj; Puri, Shurehraman; Shahi, Ramesh; Bhatta, Uttam; Khadka, Sulochana; Yadav, Gopal Kumar; Subedi, Prativa; Amgain, Kapil (Journal of Nepal Health Research Council, 2024)
Background : Sickle cell anemia is the most common hemoglobinopathy in the world. The study aimed to evaluate the iron profile and its association with socio-demographic characteristics in patients with sickle cell disease.Methods: A hospital-based descriptive cross-sectional study was conducted to know the iron profile and its socio-demographic association in patients with sickle cell disease.Results: The average serum iron, TIBC, and transferrin saturation were 16.75 ± 6.40 mcgMole/L, 69.46 ± 16.94 mcg/dl and 25.15 ± 12.51% respectively. The serum ferritin ranged from 10.00 to 3000.00 ng/ml. The proportion of participants with normal serum iron, TIBC, serum ferritin, and transferrin saturation were 86.10%, 0.00%, 33.90% and 36.40% respectively. All of the participants of this study had low TIBC (1005), and more than half of the participants had elevated serum ferritin (56.40%).Conclusions: Iron overload is a common complication of sickle cell disease. There was no association of age and sex with iron profile. The TIBC variation between the Chaudhary ethnic group compared to other ethnic groups signifies the ethnic role in the iron profile.Keywords: Ethnicity; iron overload; sickle cell disease; total iron binding capacity.